2010
DOI: 10.1093/jac/dkq204
|View full text |Cite
|
Sign up to set email alerts
|

Use of the HCP5 single nucleotide polymorphism to predict hypersensitivity reactions to abacavir: correlation with HLA-B*5701

Abstract: The use of HCP5 rs2395029 testing could be as useful as HLA-B*5701 typing to prevent the abacavir hypersensitivity reaction. Given that HCP5 testing is cheaper, less time-consuming and easier to perform than HLA typing, it may confidently replace the latter in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 6 publications
3
35
0
Order By: Relevance
“…We would like to point out that although we identified a complete LD (r 2 = 1) in our study on 300 samples of well characterized Mexican Mestizos, we advised caution when interpretating the results due to previous reports by Nolan et al [3], Colombo et al [4] and Rodríguez-Nóvoa et al [5], which demonstrated that LD is high but not complete. We did not however observe indi viduals that were HCP5 rs2395029(G)-positive and HLA-B*5701-negative; this may be due to the relatively low (2%) HLA-B*57:01 allele frequency observed and the small number of individuals included in our study.…”
mentioning
confidence: 46%
“…We would like to point out that although we identified a complete LD (r 2 = 1) in our study on 300 samples of well characterized Mexican Mestizos, we advised caution when interpretating the results due to previous reports by Nolan et al [3], Colombo et al [4] and Rodríguez-Nóvoa et al [5], which demonstrated that LD is high but not complete. We did not however observe indi viduals that were HCP5 rs2395029(G)-positive and HLA-B*5701-negative; this may be due to the relatively low (2%) HLA-B*57:01 allele frequency observed and the small number of individuals included in our study.…”
mentioning
confidence: 46%
“…For this reason, another genetic marker proposed as surrogate of the HLA-B*5701 allele and Abacavir HSR is a polymorphism located within the HLA complex P5 gene, HCP5 rs2395029. This polymorphism was found to be in high linkage disequilibrium with HLA-B*5701 by several studies [44], allowing the clinical use of the former marker as an alternative to HLA typing [44,45].…”
Section: Nucleoside Reverse Transcriptase Inhibitorsmentioning
confidence: 98%
“…In Caucasians and Hispanics, the SNP rs2395029 is in linkage disequilibrium with HLA-B*57:01 [104]. Detection of rs2395029 is associated with a sensitivity of 100% and a specificity of 99% for the identification of HLA-B*57:01 carriers.…”
Section: Genetic Screeningmentioning
confidence: 99%
“…Detection of rs2395029 is associated with a sensitivity of 100% and a specificity of 99% for the identification of HLA-B*57:01 carriers. However, despite this strong association, this disequilibrium is incomplete, and, in fact, detection of rs2395029 is associated with a positive predictive value <100% [104]. Based on the results of a Japanese study, rs9263726 (an SNP located within the PSORS1C1 gene) is in complete linkage disequilibrium with the HLA-B*58:01 allele [105], leading the authors to conclude that rs9263726 detection can be effectively used to screen for HLA-B*58:01 carriage [105].…”
Section: Genetic Screeningmentioning
confidence: 99%